Legal Protection For Investors of Government Bonds Whose Clauses Do Not Have A Maturity Period - Shandietrysno, Adrianus Jeffri; Chumaida, Zahry Vandawati; Subagyono, Bambang Sugeng Ariadi (Faculty of Law, Andalas University, 2023)
The state in running its government needs funds with the aim of national development and maintaining the stability of the country's economy. One of the funds obtained is through debt instruments, both domestic debt and foreign debt. The government avoids foreign debt, thus optimizing domestic debt with consideration so that the public can participate in raising funds for national development. With this goal, the government issued government bonds or better known as Government Bonds (SUN). Government Bonds are securities in the form of debt recognition letters in rupiah and foreign currencies guaranteed by the payment of interest and principal by the Republic of Indonesia, in accordance with the validity period. However, the SUN issued in 1950 by the government, has no perpetual bond. Unlike the SUN issued today, there is a maturity period and guaranteed by interest and principal payers as stipulated in Law Number 24 of 2002 concerning Government Bonds. Meanwhile, the SUN issued in 1950 has no time period, so it does not provide legal certainty and legal protection to holders of the 1950 SUN, even though the SUN was issued by the same government.